2018
DOI: 10.1111/hae.13446
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chromogenic factor IX assays by automated protocols

Abstract: Both commercial factor FIX CSA kits can be adapted for Stago and Sysmex automated coagulation analysers. Reagent cost and workflow practices will need to be considered. These assays are potentially more consistent than OSA in measurement of replacement FIX products in haemophilia B patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…Kershaw et al previously evaluated automated chromogenic FIX assays and found between-run CVs ranged from 1.8% to 4.5% using a Sysmex CS-2500 analyser. 8 Small differences were present, but the current study performed analyses in only a small number of assays (n = 5), so this represents a limitation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Kershaw et al previously evaluated automated chromogenic FIX assays and found between-run CVs ranged from 1.8% to 4.5% using a Sysmex CS-2500 analyser. 8 Small differences were present, but the current study performed analyses in only a small number of assays (n = 5), so this represents a limitation.…”
Section: Discussionmentioning
confidence: 88%
“…In normal plasma, the relationships between CSA and OSA showed differences, especially in high levels of FIX activity. Although a recent study showed a similar variation in the normal range of FIX:C, 8 we should consider increasing the dilution when testing FIX within the normal range or in levels exceeding the upper limit of normal range. Throughout the correlation analyses, we evaluated single-dilution analyses of Revohem FVIII and FIX.…”
Section: Revohem Fviii Includes Human Recombinant Protein Whereas Simentioning
confidence: 83%
“…The authors also acknowledge that it would have been ideal to base the primary analysis on a one‐stage clotting assay that used the same aPTT reagent for both products; however, unfortunately, there is not a single aPTT reagent that could be used to measure both products and allow a more robust head‐to‐head comparison. A previously published field study by Sommer et al showed that a one‐stage clotting assay using SynthAFax overestimates FIX activity for rFIXFc in spiked hemophilia B plasma samples, and a recent study by Kershaw et al also reported over‐recovery for rFIXFc with this aPTT reagent . Meanwhile, the field study by Sommer et al demonstrated that a one‐stage clotting assay with Actin FSL accurately reproduces the activity of rFIXFc .…”
Section: Discussionmentioning
confidence: 99%
“…Normal human plasma (NHP) standards, calibrated against the World Health Organization international FIX standard, were used to calibrate all assays. For the one‐stage clotting assays, the activated partial thromboplastin time (aPTT) reagents were selected by referring to the product label and/or published literature recommendations for each product; SynthAFax (Instrumentation Laboratory, Bedford, MA) was used for N9‐GP and Actin FSL (Siemens, Marburg, Germany) for rFIXFc. To date, chromogenic assays had not been used in any clinical trials with rFIXFc; however, given that the ROX factor IX (Rossix AB, Mölndal, Sweden) kit has been previously qualified for measuring N9‐GP, it was subsequently qualified for measuring rFIXFc in the current trial and selected as the chromogenic assay for both products.…”
Section: Methodsmentioning
confidence: 99%
“…Potency for RB by ChA was ~30% lower than by OSCA, the OSCA/ChA discrepancy with recombinant FIX has been described in a number of other studies. 7,8,23,24 For DA in the OSCAs, there was a roughly 3-fold difference between the highest potency (CK Prest) and lowest potency (SynthFax) using both S1 and S2 standards. RB also showed lower potency when assayed using SynthaFax than the other APTT reagents, underestimation of Benefix with Synthfax has been previously reported.…”
Section: Discussionmentioning
confidence: 99%